Modeling the Effect of Gauge Length on the Mechanical Properties of Chitin Whiskers Reinforced Composites (Nigerian Journal of Technology, 2021)
Mechanical properties (tensile strength and modulus) of Chitin Whiskers fibre-reinforced poly(acrylic acid) with different fibre loading and different gauge lengths are compared with theories of reinforcement. The addition of random oriented Chitin Whiskers to poly(acrylic acid) matrix increased in tensile strength and elastic modulus of the composite. There was a steady increase in tensile stress and Elastic modulus within the volume fraction range investigated. The properties of the composite at different gauge lengths were studied. Within the same volume fraction, the tensile stress decreases as the gauge length increases. It is the reverse for the Elastic Modulus. Irrespective of filler loading and the theoretical modelling equations the tensile stress can be predicted at 40 mm gauge length. For the Elastic Modulus, the prediction of the property varies within the gauge lengths investigated. At higher filler loading, a smaller gauge length is required to predict the Elastic modulus. The comparative study between the tensile stresses obtained by experiment and selected theoretical models showed that the Parallel and Series models of the Rule of Mixture produced more accurate prediction, followed by Halpin-Tsai and modified Halpin-Tsai models. Guth's model was the least as the percentage deviation from the experimental data was very high when predicting the Elastic modulus. The density of the nanocomposite films were 1.08g/cm3, 1.023, and 1.024g/cm3 respectively, for 3%, 6%, and 9% weight filler and were in agreement with the theoretical data.